An investment appraisal of international maritime assets for Malaysian Islamic financial institutions - the case for equity finance - Abdullah, Adam; Hassan, Rusni; Kassim, Salina (International Islamic University Malaysia, 2017)
The purpose of this research is to investigate the overall investment performance of international maritime assets in order to facilitate Islamic equity finance and investment involving Malaysian Islamic finance institutions, retail and also institutional investors. Shipping is a strong growth industry with about 84% of global trade carried by the international shipping industry. The problem is that Malaysian Islamic financial institutions have essentially no exposure and thus understanding of international shipping. However, shipping is a highly capital intensive industry and currently 75% of ship lending has been conducted by European banks and financed on a conventional basis. This research involves an investment analysis of a full population of historical data over a period of 20 years to evaluate maritime performance by adopting IRR, net yield and standard deviation measures of risk and return. We also develop a correlation matrix for maritime assets and compare returns to other real and financial investments. Our findings reveal that whilst earnings are volatile in comparison to capital market financial products, unlevered, tax-free returns on maritime assets are very attractive. The significance is that Islamic equity finance, rather than debt at the time-value-of-money should enable the development of international shipping in Malaysia.